Zamień ułamek na ułamki o mianownikach:
a)x² +10x +9
b) x² - 5x -6
c) x² +5x +4
d)x³+1
c)\
proszę bardzo ;)
a)
x²+10x+9=
x²+x+9x+9=
x(x+1)+9(x+1)=
(x+9)(x+1)
(x-1)/(x+1)=
(x-1)(x+9)/(x+1)(x+9)=
(x²+9x-x-9)/(x²+10x+9)=
(x²+8x-9)/(x²+10x+9)
b)
x²-5x-6=
x²+x-6x-6=
x(x+1)-6(x+1)=
(x-6)(x+1)=
(x-1)(x-6)/(x+1)(x-6)=
(x²-6x-x+6)/(x²-5x-6)=
(x²-7x+6)/(x²-5x-6)
c)x² +5x +4=
x²+x+4x+4=
x(x+1)+4(x+1)=
(x+4)(x+1)=
(x-1)(x+4)/(x+1)(x+4)=
(x²+4x-x-4)/(x²+5x+4)=
(x²+3x-4)/(x²+5x+4)
d)
x³+1=
(x+1)(x²-x+1)
(x-1)(x²-x+1)/(x+1)(x²-x+1)=
(x³-x²+x-x²+x-1)/(x³+1)=
(x³-2x²+2x-1)/(x³+1)
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
c)\![c)\ \ \frac{x-1}{x+1}=\frac{(x-1)(x+4)}{(x+1)(x+4)}=\frac{x^{2}+3x-4}{x^{2}+5x+4} c)\ \ \frac{x-1}{x+1}=\frac{(x-1)(x+4)}{(x+1)(x+4)}=\frac{x^{2}+3x-4}{x^{2}+5x+4}](https://tex.z-dn.net/?f=c%29%5C+%5C+%5Cfrac%7Bx-1%7D%7Bx%2B1%7D%3D%5Cfrac%7B%28x-1%29%28x%2B4%29%7D%7B%28x%2B1%29%28x%2B4%29%7D%3D%5Cfrac%7Bx%5E%7B2%7D%2B3x-4%7D%7Bx%5E%7B2%7D%2B5x%2B4%7D)
proszę bardzo ;)
a)
x²+10x+9=
x²+x+9x+9=
x(x+1)+9(x+1)=
(x+9)(x+1)
(x-1)/(x+1)=
(x-1)(x+9)/(x+1)(x+9)=
(x²+9x-x-9)/(x²+10x+9)=
(x²+8x-9)/(x²+10x+9)
b)
x²-5x-6=
x²+x-6x-6=
x(x+1)-6(x+1)=
(x-6)(x+1)=
(x-1)/(x+1)=
(x-1)(x-6)/(x+1)(x-6)=
(x²-6x-x+6)/(x²-5x-6)=
(x²-7x+6)/(x²-5x-6)
c)
x² +5x +4=
x²+x+4x+4=
x(x+1)+4(x+1)=
(x+4)(x+1)=
(x-1)/(x+1)=
(x-1)(x+4)/(x+1)(x+4)=
(x²+4x-x-4)/(x²+5x+4)=
(x²+3x-4)/(x²+5x+4)
d)
x³+1=
(x+1)(x²-x+1)
(x-1)/(x+1)=
(x-1)(x²-x+1)/(x+1)(x²-x+1)=
(x³-x²+x-x²+x-1)/(x³+1)=
(x³-2x²+2x-1)/(x³+1)